Effects of fluorine modification on the photocatalytic hydrogen production performance of TiO2 - Jie Hu; Xianhao Shan; Shan Wu; Pengfei Sun; Zhengyuan Gao; Zhong Ren; Xiangchao Feng; Shuai Wang (Frontiers in Chemistry)
As an efficient and environmentally friendly photocatalyst, TiO2 has garnered significant interest among researchers. However, the rapid recombination of photogenerated carriers leads to the inhibition of its photocatalytic activity. Fluorine modification has been proven to be an effective method to improve the photocatalytic performance of TiO2, leading to a multitude of research reports on this subject. Surface fluorine adsorption or lattice fluorine doping can deftly modulate the surface chemical attributes and electronic configuration of the TiO2 photocatalyst, thereby amplifying its functional performance. The role of fluorine atoms coordinated with different number titanium atoms (terminal Ti1-F, bridging Ti2-F and Ti3-F) are also discussed. This paper provides a minireview of various aspects of fluorine-modified TiO2, including its classification (surface-adsorbed fluorination, lattice-doped fluorination and Tix-F) and characterization techniques (X-ray photoelectron spectroscopy and solid-state nuclear magnetic resonance). Finally, this treatise elucidates the mechanistic impact of fluorine modification on the photocatalytic hydrogen production performance of TiO2.